Photochemical and Nonphotochemical Reactions of Phytochrome in vivo - Pratt, Lee H. (1966)
The nonphotochemical reactions of phytochrome in the coleoptiles of dark-grown corn seedlings were studied at 3 temperatures: 14°, 24°, and 34°. The data obtained show that the destruction of P(fr) is the only measurable reaction occurring; reversion of P(fr) to P(r) was not found. The Q(10)'s (2.7 and 3.5) and zero order kinetics found for the destruction reaction are consistent with the hypothesis that the reaction is enzyme-mediated. In vivo action spectra for phytochrome transformation in the coleoptiles of darkgrown corn seedlings were obtained which agree qualitatively with those obtained by other workers for phytochrome-mediated physiological responses and in vitro action spectra. In vivo conversion of phytochrome by blue light, as determined from spectrophotometric measurements of phytochrome itself, is reported. Action peaks for P(r) were found at 667 mμ and in the blue in the region of 400 mμ, with a broad shoulder from 590 mμ to 640 mμ. Action peaks for P(fr) were found at 725 mμ and in the blue in the region of 400 mμ with a minor peak at 670 mμ, and a broad shoulder from 590 mμ to 640 mμ. The ratio of the quantum efficiencies of P(r) at 667 mμ and P(fr) at 725 mμ (Φ(r667)/Φ(fr725)) was estimated to be 1.0.